Transformational School Leadership and Quality Management Practices: Insights from a Public Primary School in Indonesia - Ilmi Firrizkiyah; Rizal Rizal; Surahman Wilade; Nashrullah Nashrullah; Roberto Rolly Bulalong (Papanda Publisher, 2026)
Transformational leadership has been widely recognized as a key driver of school improvement; however, limited research has examined how it is operationalized within school quality management processes, particularly at the primary education level in public school contexts. This study employed a qualitative case study design, supplemented by descriptive survey data, to investigate how a principal's transformational leadership contributes to the implementation of school quality management at SD Negeri 1 Pembina Kintom, Indonesia. Data were collected from 16 participants through semi-structured interviews, observations, document analysis, and a validated perception questionnaire (Cronbach's α = 0.87–0.84), and were analyzed using Miles and Huberman's interactive model alongside descriptive frequency analysis. The principal demonstrated strong transformational leadership across all four dimensions: idealized influence (97.00%), inspirational motivation (70.83%), intellectual stimulation (70.00%), and individualized consideration (69.58%). School quality management was consistently rated high across input (62.50%), process (72.91%), and output–outcome (69.60%) components. Cross-analysis revealed that specific leadership dimensions systematically animated corresponding quality management components. Conclusion Transformational leadership functioned not merely alongside quality management but as its operational mechanism, providing practical guidance for principals and policymakers seeking sustainable school improvement.